Prototyping an Atlas of Early Modern English Drama: An Experiment on DraCor Data - Giovannini, Luca; Wagner, Andreas (AIUCD 2025: Diversità, equità e inclusione (AIUCD 2025), 2025)
This short contribution leverages the recently released English Drama Corpus from the DraCor project (Fischer et al. 2019) to create an interactive map of geographical references in early modern English drama by means of Named Entity Recognition (NER) tools. The prototype allows to visualise interesting patterns in the playwrights’ use of locations while underscoring the need of improved NLP tools to effectively tackle geospatial research questions about early modern literatur
Keywords: early modern drama; spatial humanities; geocoding; digital cartography